T-PLL Presenting with an Indolent Course - Arsa Thammahong; Narittee Sukswai; Chantana Polprasert (Case Reports in Hematology)
T-cell prolymphocytic leukemia (T-PLL) is a rare, mature T-cell leukemia which usually presents with aggressive behavior. We report an asymptomatic T-PLL patient diagnosed by clinical features, lymphocyte morphology, and flow cytometry. Incidentally, she was found to have lymphocytosis and lymphadenopathy. Flow cytometry from blood revealed an abnormally increased CD4+ T-cell population. T-cell receptor clonality assessment by next-generation sequencing revealed a dominant clone in the ß-chain constant region. No pathogenic mutations in 25 lymphoma-related genes were found. Due to her asymptomatic T-PLL disease, we observed her clinical situation and blood count every three months for at least one year.